2003
DOI: 10.1523/jneurosci.23-12-04888.2003
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of δ-Opioid Receptor Trafficking via μ-Opioid Receptor Stimulation: Evidence from μ-Opioid Receptor Knock-Out Mice

Abstract: We recently demonstrated that prolonged treatment with morphine increases the antinociceptive potency of the delta-opioid receptor (deltaOR) agonist deltorphin and promotes cell surface targeting of deltaORs in neurons of the dorsal horn of the rat spinal cord (Cahill et al., 2001b). In the present study we examined whether these effects were mediated selectively via muOR. Using the same intermittent treatment regimen as for morphine, we found that methadone and etorphine, but not fentanyl, enhanced [D-Ala2]-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
128
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(139 citation statements)
references
References 76 publications
9
128
1
1
Order By: Relevance
“…We previously demonstrated that prolonged treatment of rodents with OR agonists including morphine induced a selective increase in cell surface density of ␦OR (Cahill et al, 2001b;Morinville et al, 2003) and internalization of ␦OR agonists in neurons of layers I-VI of the lumbar spinal cord (Morinville et al, 2004a). We also showed that chronic inflammation resulting from the injection of CFA into the rat hind paw similarly enhanced, bilaterally, the membrane density of ␦OR in neurons of the dorsal horn .…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…We previously demonstrated that prolonged treatment of rodents with OR agonists including morphine induced a selective increase in cell surface density of ␦OR (Cahill et al, 2001b;Morinville et al, 2003) and internalization of ␦OR agonists in neurons of layers I-VI of the lumbar spinal cord (Morinville et al, 2004a). We also showed that chronic inflammation resulting from the injection of CFA into the rat hind paw similarly enhanced, bilaterally, the membrane density of ␦OR in neurons of the dorsal horn .…”
Section: Discussionmentioning
confidence: 86%
“…The CFA-induced up-regulation of cell surface ␦OR in spinal cord neurons involves the participation of OR as it can no longer be elicited in OR knockout mice (Morinville et al, 2004b). The effect of chronic inflammation on ␦OR trafficking is therefore akin to that of prolonged treatment with OR-preferring agonists (including morphine, fentanyl, methadone and etorphine), which was shown to induce a selective membrane recruitment of ␦OR in neurons of layers I-VI of the rat lumbar spinal cord (Cahill et al, 2001b;Morinville et al, 2003). As in animals with chronic inflammation, this increased density of cell surface ␦OR translates into a potentiation of the antinociceptive properties of deltorphin II injected intrathecally (i.t.)…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The heterodimerization of different GPCRs can result in the modulation of their function and/or the redistribution of their subcellular locations [17][18][19][20] . It was documented that 2-adrenergic agonist isoproterenol could induce the internalization of opioid receptors through the hetero-dimer of 2-adrenergic receptor and opioid receptor [20] .…”
Section: Ach Induced the Hetero-regulation Of D1 Receptorsmentioning
confidence: 99%
“…3.4 D1R and D5R co-expressed in the same cell kept their distinct trafficking properties Dopamine D1 receptors can not only form the homodimer [16,17] , but also form the heterodimer with other GPCRs [17,18] . The heterodimerized GPCRs can result in the mutual modulation of their function and/or the redistribution of their subcellular locations [17][18][19][20] .…”
mentioning
confidence: 99%